Effect of Prenatal and Neonatal Anti‐Androgen Flutamide Treatment on Aquaporin 5 Expression in the Adult Porcine Ovary. Issue 1 (10th December 2015) - Grzesiak, M; Knapczyk‐Stwora, K; Luck, MR; Mobasheri, A; Slomczynska, M
Contents: The growth of ovarian follicles is accompanied by fluid‐filled antrum formation. Water movement within the follicular wall is predominantly transcellular via membranous water channels named aquaporins (AQPs). Androgens are important regulators of mammalian folliculogenesis, and their prenatal and/or neonatal deficiency affects female fertility in adulthood. Therefore, this study was performed to determine whether gestational or neonatal exposure to the anti‐androgen flutamide influences androgen‐dependent AQP5 expression in pre‐antral and large antral follicles of adult pigs. Flutamide was injected into pregnant gilts between days 80 and 88 of gestation and into female piglets between days 2 and 10 post‐natally. The ovaries were collected from flutamide‐treated and non‐treated (control) sexually mature pigs. In pre‐antral follicles, AQP5 mRNA and protein levels were both downregulated following maternal (p < 0.01 and p < 0.01, respectively) and neonatal (p < 0.01 and p < 0.01, respectively) flutamide exposure. Likewise, the expression of mRNA (p < 0.01 and p < 0.001, respectively) and protein (p < 0.05 and p < 0.01, respectively) for AQP5 were diminished in large antral follicles in both groups. Immunohistochemistry showed decreased intensity of AQP5 immunoreaction in pre‐antral (p < 0.01) and large antral (p < 0.001) follicles following flutamide treatment. Moreover, radioimmunological analysis revealed that changes observed in AQP5 expression corresponded with diminished follicular androgens production after both maternal (p < 0.05 and p < 0.05, respectively) and neonatal (p < 0.05 and p < 0.01, respectively) flutamide administration. Therefore, AQP5 appears to be a potential regulator of follicular fluid accumulation, under androgen control, and may be a key factor in antral follicle growth.